PERAN PERPUSTAKAAN KOMUNITAS PADA PEMBERDAYAAN MASYARAKAT : STUDI KASUS TAMAN BACA KESIMAN - Marisa, Desy; Haryanti, Ni Putu Premierita; Kastawa, Made (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2018)
The purpose of this study is to determine the empowerment of the community conducted by Taman Baca Kesiman. This research is qualitative research with case study method. Data collection techniques used are interviews, observation and document analysis. Informants from this study amounted to 6 (six) people, 1 (one) owner, 2 (two) managers, and 3 (three) visitors. This research was conducted during February-April 2018. This research uses the stages or components of qualitative research data analysis.The results of this study indicate that the form of empowerment in the taman baca kesiman is through discussion programs, berdendang and cinecoda, the community is not only empowered through the program, but there are also gardens and kitchens that become a place of community empowerment. Stages of community empowerment are preparation, assessment, alternative planning of programs or activities, formulation of action plans, implementation of programs or activities, evaluation and termination. In every activity not many obstacles are perceived because the manager does not consider obstacles as an obstacle. Keywords: empowerment, community library, community